2020
DOI: 10.1084/jem.20201707
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes are activated in response to SARS-CoV-2 infection and are associated with COVID-19 severity in patients

Abstract: Severe cases of COVID-19 are characterized by a strong inflammatory process that may ultimately lead to organ failure and patient death. The NLRP3 inflammasome is a molecular platform that promotes inflammation via cleavage and activation of key inflammatory molecules including active caspase-1 (Casp1p20), IL-1β, and IL-18. Although participation of the inflammasome in COVID-19 has been highly speculated, the inflammasome activation and participation in the outcome of the disease are unknown. Here we demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

48
781
2
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 683 publications
(848 citation statements)
references
References 33 publications
48
781
2
17
Order By: Relevance
“…Moreover, the extent of systemic inflammation is further modified by adipokines, hepatokines, myokines, lipokines, branched-chain amino acids, and microbial metabolites, which may circulate at abnormal levels in some people with T2D or obesity. Collectively, these acquired abnormalities broadly impair cellular immune function, likely contributing to enhanced activation of the NLRP3 inflammasome, and a greater susceptibility to infection in vulnerable individuals ( Rodrigues et al., 2021 ). There is considerable interest in whether the expression of viral entry factors essential for SARS-CoV-2 infectivity is enhanced in one or more tissues in people with T2D or obesity ( Figure 1 ); however, the available data are inconclusive ( Drucker, 2020 ).…”
Section: Susceptibility Of People With Diabetes and Obesity To Infectmentioning
confidence: 99%
“…Moreover, the extent of systemic inflammation is further modified by adipokines, hepatokines, myokines, lipokines, branched-chain amino acids, and microbial metabolites, which may circulate at abnormal levels in some people with T2D or obesity. Collectively, these acquired abnormalities broadly impair cellular immune function, likely contributing to enhanced activation of the NLRP3 inflammasome, and a greater susceptibility to infection in vulnerable individuals ( Rodrigues et al., 2021 ). There is considerable interest in whether the expression of viral entry factors essential for SARS-CoV-2 infectivity is enhanced in one or more tissues in people with T2D or obesity ( Figure 1 ); however, the available data are inconclusive ( Drucker, 2020 ).…”
Section: Susceptibility Of People With Diabetes and Obesity To Infectmentioning
confidence: 99%
“…A number of studies, particularly those in rodents, have suggested that activation of the NLRP3 inflammasome is important in different sepsis models (Danielski et al, 2020), and there has been much speculation that NLRP3 would be linked to the pathogenesis of COVID-19. The Zamboni paper (Rodrigues et al, 2020) provides nice evidence to support this hypothesis (see figure) in SARS-CoV-2-infected patients; however, it also suggests a role for other inflammasomes in the pathogenesis of this disease. This suggests that inhibition of NLRP3 alone may have limited usefulness in COVID-19 sepsis, although its importance in other human septic syndromes remains to be determined.…”
mentioning
confidence: 79%
“…In this issue of JEM, Rodrigues et al (2020) show that activation of inflammasomes by SARS-CoV-2 infection is linked with COVID-19 disease severity in patients, potentially providing new therapeutic avenues for this intractable condition. Inflammasomes are macromolecular inflammatory signaling complexes that may be canonical (composed of a receptor, such as a nucleotide oligomerization domain leucine rich repeat receptor [NLR] or AIM-2 like receptor; an adaptor [ASC]; and an effector [caspase 1]) or noncanonical (composed of caspase 4 or 5 in humans or caspase 11 in mice; Broz and Dixit, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An upsurge of IL-1β, IL-18, and LDH (Lactate dehydrogenase) has been reported in sera of COVID-19 patients, which hints the involvement of the inflammasome network [ 107 , 108 , 109 ]. Similarly, a recent study conducted on COVID-19 patients reveals the activation of the NLRP3 inflammasome [ 110 ]. In this study, microscopic analysis in combination with luminescent assays show the formation of NLRP3 and ASC puncta, caspase-1 activation, and IL-1β secretion in PBMCs (Peripheral blood mononuclear cells) of COVID-19 patients during the disease and in postmortem lung tissues [ 110 ].…”
Section: Nlrp3mentioning
confidence: 91%